The Arabidopsis thylakoid chloride channel ClCe regulates ATP availability for light-harvesting complex II protein phosphorylation - Dukic, Emilija; Gollan, Peter J.; Grebe, Steffen; Paakkarinen, Virpi; Herdean, Andrei; Aro, Eva-Mari; Spetea, Cornelia (Frontiers in Plant Science, 2022)
Coping with changes in light intensity is challenging for plants, but well-designed mechanisms allow them to acclimate to most unpredicted situations. The thylakoid K+/H+ antiporter KEA3 and the voltage-dependent Cl− channel VCCN1 play important roles in light acclimation by fine-tuning electron transport and photoprotection. Good evidence exists that the thylakoid Cl− channel ClCe is involved in the regulation of photosynthesis and state transitions in conditions of low light. However, a detailed mechanistic understanding of this effect is lacking. Here we report that the ClCe loss-of-function in Arabidopsis thaliana results in lower levels of phosphorylated light-harvesting complex II (LHCII) proteins as well as lower levels of the photosystem I-LHCII complexes relative to wild type (WT) in low light conditions. The phosphorylation of the photosystem II core D1/D2/CP43 proteins was less affected either in low or high light conditions. In low light conditions, the steady-state levels of ATP synthase conductivity and of the total proton flux available for ATP synthesis were lower in ClCe loss-of-function mutants, but comparable to WT at standard and high light intensity. As a long-term acclimation strategy, expression of the ClCe gene was upregulated in WT plants grown in light-limiting conditions, but not in WT plants grown in standard light even when exposed for up to 8 h to low light. Taken together, these results suggest a role of ClCe in the regulation of the ATP synthase activity which under low light conditions impacts LHCII protein phosphorylation and state transitions.